Preparation method of novel power type lithium iron phosphate positive electrode material
Through the dry preparation method, nearly spherical ferrous oxalate is synthesized and dry mixed, which solves the problems of high preparation cost and low compaction of lithium iron phosphate cathode materials in the existing technology, and achieves high compaction density and low energy consumption. production effect.
Patent Information
- Application Number
- CN202411489618.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-24
AI Technical Summary
The existing preparation methods of lithium iron phosphate positive electrode materials have problems such as high cost, low compaction, and large energy consumption and large area of wet spray drying equipment.
The method of preparing method of dry method is used to synthesize close -spherical oxalic acid iron, and dry mixing in the drum -type drying machine, and then prepare high -voltage and density iron phosphate with high -pressure density iron phosphates through pressing the bleach, sintering and crushing process. Material.
The high -pressure solid density of the lithium iron phosphate positive pole material is realized, the production cost and energy consumption are reduced, and the demand for equipment and venue is reduced.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion battery materials, and in particular to a method for preparing a novel power-type lithium iron phosphate positive electrode material. Background Art
[0002] With the development of new energy vehicles, higher requirements are placed on the performance, capacity and safety of power batteries. As the cathode material with the highest market share, lithium iron phosphate material has high capacity and safety. In addition, lithium iron phosphate prepared by the ferrous oxalate method can achieve excellent performance in power performance due to the presence of nano-scale particles. However, lithium iron phosphate prepared by the ferrous oxalate method has the problems of high cost and low compaction.
[0003] Secondly, it was found during production that the wet spray drying method requires a lot of equipment and management costs for solvent transportation, recovery, and safe management of alcohol solvents. The spray drying equipment consumes a lot of energy and occupies a large area. Therefore, in the context of reducing costs and increasing efficiency, using a dry method to prepare lithium iron phosphate is a direction that can be explored. Summary of the invention
[0004] In view of the above problems existing in the prior art, the present invention provides a method for preparing a novel power-type lithium iron phosphate positive electrode material, which is used to overcome the above defects in the prior art.
[0005] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is as follows:
[0006] A method for preparing a novel power-type lithium iron phosphate positive electrode material comprises the following steps:
[0007] In the first step, the iron source is dissolved in sulfuric acid with a concentration of 2 to 5 mol / L to prepare a ferrous mother solution, wherein the concentration of Fe2+ in the ferrous mother solution is 1.2 to 1.5 mol / L;
[0008] The second step is to put the ferrous mother liquor produced in the first step into a stirrer, add additives into the stirrer at a speed of 50-90 rpm, stir for 30 minutes, control the solution temperature between 50 and 100° C., then drop oxalic acid solution into the stirrer, stir for 120-150 minutes after adding the oxalic acid solution, and then obtain a nearly spherical ferrous oxalate material after filter pressing, washing and filtering, and drying;
[0009] The third step is to put the ferrous oxalate produced in the second step, lithium dihydrogen phosphate, carbon source, auxiliary materials and zirconium balls into a drum dry mixer according to a certain proportion, and stir the dry mixer at a speed of 150 to 400 rpm for 1 to 2 hours;
[0010] In the fourth step, after stirring, the baffle on one side of the drum dry mixer is opened, and the stirred material is discharged to the vibrating screen located below the baffle of the drum dry mixer. The zirconium balls in the material are sieved out by the vibrating screen to obtain lithium iron phosphate precursor powder. The sieved lithium iron phosphate precursor powder is sent to the silo through a conveyor belt;
[0011] The fifth step is to transport the lithium iron phosphate precursor powder in the silo to the molding machine below it, where the lithium iron phosphate precursor powder is pressed into a green body and loaded into a sagger, and then sent to a roller furnace for sintering;
[0012] In the sixth step, after sintering, the sagger is turned over, and the sintered embryo body falls into the mixer located below the roller furnace outlet. The sintered embryo body is then crushed into powder by the rotating blade of the mixer. The crushed powder is then transported to the air flow mill for further crushing to finally obtain lithium iron phosphate positive electrode material.
[0013] In one embodiment, the iron source in the first step is iron wire or iron powder with a purity of 99.9%.
[0014] In one embodiment, the additive in the second step is one or more of ethylene glycol, glycerol, β-cyclodextrin, maltose, oligofructose, and disodium tartrate, and the additive is added according to the volume of the mother solution to control its concentration to 1 mol / L;
[0015] Add 2 mol / L oxalic acid solution until the pH of the entire mixture is ≤1.
[0016] In one embodiment, the carbon source in the third step is one or more of polyethylene glycol 1000-4000, glucose, citric acid, and sucrose.
[0017] In one embodiment, the auxiliary material in the third step is one or more of starch, ammonium carbonate, coal powder, titanium oxide, vanadium oxide, and niobium oxide, and the addition amount thereof is 0.5-2% of the total mass;
[0018] Starch, ammonium carbonate and coal powder will produce gas and decompose at less than 200℃, leaving a certain channel for the subsequent decomposition of ferrous oxalate to avoid the rapid splitting of the green body. Titanium oxide, vanadium oxide and niobium oxide can improve the low ion conductivity of lithium iron phosphate positive electrode materials.
[0019] In one embodiment, the ferrous oxalate and lithium dihydrogen phosphate in the third step are mixed in a ratio of Fe:Li=1:1.02-1.05, 8% polyethylene glycol 4000, 2% glucose, and 1% starch are added according to the weight of the first two, and zirconium balls with a particle size of 0.6-1 mm are added at a ball-to-material ratio of 1:5.
[0020] In one of the embodiments, the working pressure of the molding machine in the fifth step is between 40 and 60 MPa.
[0021] In one of the embodiments, when the roller furnace in the fifth step is operating, the operating temperature is between 750-770° C. for sintering for 9-12 hours, and the embryo inside is protected by nitrogen.
[0022] In one embodiment, the particle size of the lithium iron phosphate positive electrode material finally obtained in the sixth step is between 1 and 1.5 μm.
[0023] In one embodiment, a stirring rod is disposed inside the drum-type dry mixer, and the direction of rotation of the drum is opposite to the direction of rotation of the stirring rod.
[0024] Compared with the prior art, the present invention provides a novel method for preparing a power-type lithium iron phosphate positive electrode material. By synthesizing nearly spherical small particles of ferrous oxalate, dry mixing them in a special mixer, and then pressing them into blanks, calcining and crushing them, a lithium iron phosphate positive electrode material with a compaction density greater than 2.7 can be prepared. On the other hand, due to the use of a dry mixing process, the consumption of the medium in the wet process is saved, and there is no need to use spray drying equipment, which greatly saves energy, cost and site expenses. DETAILED DESCRIPTION
[0025] The present invention is further described in detail below in conjunction with the embodiments:
[0026] Example 1
[0027] The first step is to dissolve iron powder with a purity of 99.9% in sulfuric acid with a concentration of 2 to 5 mol / L to prepare a ferrous mother liquor, wherein the concentration of Fe2+ in the ferrous mother liquor is 1.2 to 1.5 mol / L;
[0028] The second step is to put the ferrous mother liquor produced in the first step into a stirrer, add β-cyclodextrin into the stirrer at a speed of 50 to 90 rpm, add β-cyclodextrin according to the volume of the mother liquor to control its concentration to 1 mol / L, stir for 30 minutes, control the solution temperature at 80°C, add 2 mol / L oxalic acid solution into the stirrer until the pH of the whole mixture is ≤1, stir for 150 minutes after adding the oxalic acid solution, and then obtain a nearly spherical ferrous oxalate material after filter pressing, washing, filtering and drying;
[0029] The third step is to mix the ferrous oxalate produced in the second step with lithium dihydrogen phosphate in a ratio of Fe:Li=1:1.05, add 8% polyethylene glycol 4000, 2% glucose, 1% starch according to the weight of the first two, and add 0.6-1mm zirconium balls in a ball-to-material ratio of 1:5, and put them into a drum dry mixer, and stir the dry mixer at a speed of 150-400rpm for 2h;
[0030] In the fourth step, after stirring, the baffle on one side of the drum dry mixer is opened, and the stirred material is discharged to the vibrating screen located below the baffle of the drum dry mixer. The zirconium balls in the material are sieved out by the vibrating screen to obtain lithium iron phosphate precursor powder. The sieved lithium iron phosphate precursor powder is sent to the silo through a conveyor belt;
[0031] The fifth step is to transport the lithium iron phosphate precursor powder in the silo to the molding machine below it. The lithium iron phosphate precursor powder is pressed into a green body in the molding machine and loaded into a sagger. The working pressure of the molding machine is between 40 and 60 MPa. Then, the green body is sent to a roller furnace for sintering. When the roller furnace is working, the working temperature is 750°C for 9-12 hours, and the green body inside is protected by nitrogen.
[0032] In the sixth step, after sintering, the sagger is turned over, and the sintered embryo body falls into the mixer located below the roller furnace outlet, and then the sintered embryo body is crushed into powder by the rotating blade of the mixer, and then the crushed powder is conveyed to the air flow mill for further crushing, and finally the lithium iron phosphate positive electrode material with a particle size between 1 and 1.5 μm is obtained.
[0033] Example 2
[0034] The first step is to dissolve iron powder with a purity of 99.9% in sulfuric acid with a concentration of 2 to 5 mol / L to prepare a ferrous mother liquor, wherein the concentration of Fe2+ in the ferrous mother liquor is 1.2 to 1.5 mol / L;
[0035] The second step is to put the ferrous mother liquor produced in the first step into a stirrer, add glycerol into the stirrer at a speed of 50 to 90 rpm, add glycerol according to the volume of the mother liquor to control its concentration to 1 mol / L, stir for 30 minutes, control the solution temperature at 50°C, add 2 mol / L oxalic acid solution into the stirrer until the pH of the whole mixture is ≤1, stir for 150 minutes after adding the oxalic acid solution, and then obtain a nearly spherical ferrous oxalate material after filter pressing, washing, filtering and drying;
[0036] The third step is to mix the ferrous oxalate produced in the second step with lithium dihydrogen phosphate in a ratio of Fe:Li=1:1.05, add 8% polyethylene glycol 4000, 2% glucose, 1% coal powder according to the weight of the first two, and add 0.6-1mm zirconium balls in a ball-to-material ratio of 1:5, and put them into a drum dry mixer, and stir the dry mixer at a speed of 150-400rpm for 2h;
[0037] In the fourth step, after stirring, the baffle on one side of the drum dry mixer is opened, and the stirred material is discharged to the vibrating screen located below the baffle of the drum dry mixer. The zirconium balls in the material are sieved out by the vibrating screen to obtain lithium iron phosphate precursor powder. The sieved lithium iron phosphate precursor powder is sent to the silo through a conveyor belt;
[0038] The fifth step is to transport the lithium iron phosphate precursor powder in the silo to the molding machine below it. The lithium iron phosphate precursor powder is pressed into a green body in the molding machine and loaded into a sagger. The working pressure of the molding machine is between 40 and 60 MPa. Then, the green body is sent to a roller furnace for sintering. When the roller furnace is working, the working temperature is 770°C for 9-12 hours, and the green body inside is protected by nitrogen.
[0039] In the sixth step, after sintering, the sagger is turned over, and the sintered embryo body falls into the mixer located below the roller furnace outlet, and then the sintered embryo body is crushed into powder by the rotating blade of the mixer, and then the crushed powder is conveyed to the air flow mill for further crushing, and finally the lithium iron phosphate positive electrode material with a particle size between 1 and 1.5 μm is obtained.
[0040] Example 3
[0041] The first step is to dissolve iron powder with a purity of 99.9% in sulfuric acid with a concentration of 2 to 5 mol / L to prepare a ferrous mother liquor, wherein the concentration of Fe2+ in the ferrous mother liquor is 1.2 to 1.5 mol / L;
[0042] The second step is to put the ferrous mother liquor produced in the first step into a stirrer, add β-cyclodextrin into the stirrer at a speed of 50 to 90 rpm, add β-cyclodextrin according to the volume of the mother liquor to control its concentration to 1 mol / L, stir for 30 minutes, control the solution temperature at 80°C, add 2 mol / L oxalic acid solution into the stirrer until the pH of the whole mixture is ≤1, stir for 150 minutes after adding the oxalic acid solution, and then obtain a nearly spherical ferrous oxalate material after filter pressing, washing, filtering and drying;
[0043] The third step is to mix the ferrous oxalate produced in the second step with lithium dihydrogen phosphate in a ratio of Fe:Li=1:1.05, add 8% polyethylene glycol 1000, 2% glucose, 1% coal powder according to the weight of the first two, and add 0.6-1mm zirconium balls in a ball-to-material ratio of 1:5, and put them into a drum dry mixer, and stir the dry mixer at a speed of 150-400rpm for 2h;
[0044] In the fourth step, after stirring, the baffle on one side of the drum dry mixer is opened, and the stirred material is discharged to the vibrating screen located below the baffle of the drum dry mixer. The zirconium balls in the material are sieved out by the vibrating screen to obtain lithium iron phosphate precursor powder. The sieved lithium iron phosphate precursor powder is sent to the silo through a conveyor belt;
[0045] The fifth step is to transport the lithium iron phosphate precursor powder in the silo to the molding machine below it. The lithium iron phosphate precursor powder is pressed into a green body in the molding machine and loaded into a sagger. The working pressure of the molding machine is between 40 and 60 MPa. Then, the green body is sent to a roller furnace for sintering. When the roller furnace is working, the working temperature is 750°C for 9-12 hours, and the green body inside is protected by nitrogen.
[0046] In the sixth step, after sintering, the sagger is turned over, and the sintered embryo body falls into the mixer located below the roller furnace outlet, and then the sintered embryo body is crushed into powder by the rotating blade of the mixer, and then the crushed powder is conveyed to the air flow mill for further crushing, and finally the lithium iron phosphate positive electrode material with a particle size between 1 and 1.5 μm is obtained.
[0047] Comparative Example 1
[0048] Purchase common ferrous oxalate on the market, and use the same lithium dihydrogen phosphate as in Example 1, mix them in a ratio of Fe:Li=1:1.05, add 8% polyethylene glycol 4000 and 2% glucose by weight of the first two, and then use wet ball milling, use anhydrous ethanol as the liquid medium, ball mill to a particle size of 1-2μm and then spray dry. The sprayed powder is sintered in a roller furnace, protected by a nitrogen atmosphere, and the sintering temperature is maintained at 760-780℃. The sintered material is pulverized by air flow and graded to a particle size of 1-1.5μm to obtain a lithium iron phosphate positive electrode material.
[0049] The samples of Examples 1 to 3 and Comparative Example 1 were subjected to electrical performance tests and compaction performance tests, and the results are shown in the following table: It was found that based on the use of the same materials, Comparative Example 1 used a wet-process prepared lithium iron phosphate positive electrode material, and after adjustment and optimization, the best performance was 3T and the compaction density was 2.65 g / cm 3, 0.1C discharge capacity is 160.95mAh / g. According to the data of Comparative Example 1, although the wet method for preparing lithium iron phosphate positive electrode material has excellent electrical properties, it is difficult to improve the compaction density, and the use of anhydrous ethanol increases the cost. Compared with the dry method, the process cost of the wet method is 20% higher and has higher requirements on equipment.
[0050]
[0051] The present invention provides a novel method for preparing a power-type lithium iron phosphate positive electrode material, which improves the compaction density of lithium iron phosphate produced by the ferrous oxalate method while reducing production costs by adjusting the ferrous oxalate morphology and matching the corresponding process method. On the other hand, the present invention optimizes the dry process and finds that the dry process has unique advantages in preparing lithium iron phosphate positive electrode materials with high compaction density, namely, the phosphorus source and the iron source can be better bonded during ball milling collision in a dry state.
[0052] The novel method for preparing a power-type lithium iron phosphate positive electrode material provided by the present invention does not require the use of spray drying equipment, so the production site and plant construction costs can be reduced by 10%; at the same time, due to the use of a dry mixing method, the medium recovery system, pipeline transportation system, alcohol-based medium supporting flammable and explosive liquid safety protection system and other equipment in the wet process are saved, so the equipment cost can be reduced by about 20%, and further, the subsequent maintenance cost can also be reduced.
[0053] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0054] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a new type of power-type lithium iron phosphate positive electrode material, characterized in that: The following steps are involved: In the first step, the iron source is dissolved in sulfuric acid with a concentration of 2 to 5 mol / L to prepare a ferrous mother liquor. 2+ The concentration is 1.2~1.5mol / L; The second step is to put the ferrous mother liquor produced in the first step into a stirrer, add additives into the stirrer at a speed of 50-90 rpm, stir for 30 minutes, control the solution temperature between 50 and 100° C., then drop oxalic acid solution into the stirrer, stir for 120-150 minutes after adding the oxalic acid solution, and then obtain a nearly spherical ferrous oxalate material after filter pressing, washing and filtering, and drying; The third step is to put the ferrous oxalate produced in the second step, lithium dihydrogen phosphate, carbon source, auxiliary materials and zirconium balls into a drum dry mixer according to a certain proportion, and stir the dry mixer at a speed of 150 to 400 rpm for 1 to 2 hours; In the fourth step, after stirring, the baffle on one side of the drum dry mixer is opened, and the stirred material is discharged to the vibrating screen located below the baffle of the drum dry mixer. The zirconium balls in the material are sieved out by the vibrating screen to obtain lithium iron phosphate precursor powder. The sieved lithium iron phosphate precursor powder is sent to the silo through a conveyor belt; The fifth step is to transport the lithium iron phosphate precursor powder in the silo to the molding machine below it, where the lithium iron phosphate precursor powder is pressed into a green body and loaded into a sagger, and then sent to a roller furnace for sintering; In the sixth step, after sintering, the sagger is turned over, and the sintered embryo body falls into the mixer located below the roller furnace outlet. The sintered embryo body is then crushed into powder by the rotating blade of the mixer. The crushed powder is then transported to the air flow mill for further crushing to finally obtain lithium iron phosphate positive electrode material.
2. A method for preparing a novel power-type lithium iron phosphate positive electrode material as claimed in claim 1, characterized in that: The iron source in the first step is iron wire or iron powder with a purity of 99.9%.
3. A method for preparing a novel power-type lithium iron phosphate positive electrode material as claimed in claim 1, characterized in that: The additive in the second step is one or more of ethylene glycol, glycerol, β-cyclodextrin, maltose, oligofructose, and disodium tartrate, and the additive is added according to the volume of the mother liquor to control its concentration to be 1 mol / L; Add 2 mol / L oxalic acid solution until the pH of the entire mixture is ≤1.
4. A method for preparing a novel power-type lithium iron phosphate positive electrode material as claimed in claim 1, characterized in that: The carbon source in the third step is one or more of polyethylene glycol 1000-4000, glucose, citric acid and sucrose.
5. A method for preparing a novel power-type lithium iron phosphate positive electrode material as claimed in claim 4, characterized in that: The auxiliary materials in the third step are one or more of starch, ammonium carbonate, coal powder, titanium oxide, vanadium oxide and niobium oxide, and the addition amount thereof is 0.5-2% of the total mass.
6. A method for preparing a novel power-type lithium iron phosphate positive electrode material as claimed in claim 5, characterized in that: The ferrous oxalate and lithium dihydrogen phosphate in the third step are mixed in a ratio of Fe:Li=1:1.02-1.05, 8% polyethylene glycol 4000, 2% glucose, and 1% starch are added according to the weight of the first two, and zirconium balls with a particle size of 0.6-1 mm are added at a ball-to-material ratio of 1:
5.
7. The method for preparing a novel power-type lithium iron phosphate positive electrode material according to claim 1, characterized in that: In the fifth step, the working pressure of the molding machine is between 40 and 60 MPa.
8. The method for preparing a novel power-type lithium iron phosphate positive electrode material according to claim 1, characterized in that: When the roller furnace in the fifth step is working, the working temperature is between 750-770° C. for sintering for 9-12 hours, and the embryo inside is protected by nitrogen.
9. The method for preparing a novel power-type lithium iron phosphate positive electrode material according to claim 1, characterized in that: The particle size of the lithium iron phosphate positive electrode material finally obtained in the sixth step is between 1 and 1.5 μm.
10. The method for preparing a novel power-type lithium iron phosphate positive electrode material according to claim 1, characterized in that: A stirring rod is arranged inside the drum-type dry mixer, and the rotation direction of the drum is opposite to the rotation direction of the stirring rod.
Citation Information
Cited By
High-compaction lithium iron phosphate as well as preparation method and application thereof
CN122561882A